2011
DOI: 10.1093/annonc/mdq458
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related fatigue: a practical review

Abstract: Fatigue is an exceedingly common often treatable problem in cancer patients that profoundly affects all aspects of quality of life. Prevalence estimates have ranged from 50% to 90% of cancer patients overall. After addressing reversible or treatable contributing factors, such as hypothyroidism, anemia, sleep disturbance, pain, emotional distress, climacterium, medication adverse events, metabolic disturbances, or organ dysfunction such as heart failure, myopathy, and pulmonary fibrosis, patients may be screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(151 citation statements)
references
References 90 publications
6
131
1
13
Order By: Relevance
“…Anemia is one of the main reversible causes of fatigue (Campos et al, 2011). It has been shown that an Hb level >12 g/ dl improves fatigue and quality of life, and even in mild anemia (Hb level between 10-12 g/dl) there is a marked increase in fatigue (Cella, 1997).…”
Section: 4251 Blood Transfusion At the End Of Life For Cancer Patienmentioning
confidence: 99%
“…Anemia is one of the main reversible causes of fatigue (Campos et al, 2011). It has been shown that an Hb level >12 g/ dl improves fatigue and quality of life, and even in mild anemia (Hb level between 10-12 g/dl) there is a marked increase in fatigue (Cella, 1997).…”
Section: 4251 Blood Transfusion At the End Of Life For Cancer Patienmentioning
confidence: 99%
“…Como os valores do IGI apresentaram níveis elevados na população que apresenta má qualidade de sono, é perceptível a existência do efeito deletério da quimioterapia sobre o sono, muito por causa de alguns agentes quimioterapêuticos induzirem dores e formarem uma relação com a insônia 15 . Embora possa estar ligada também a outros fatores, como possíveis reações a diferentes mecanismos -como efeitos psicológicos ou uma resposta imune 16 -, é possível sugerir que a relação de insônia e o nível de PSQI-Br está associada a fatores secundários como dores, náuseas e a necessidade de ir ao banheiro durante a noite.…”
Section: Discussionunclassified
“…Fatigue can persist for years after treatment 36 , but can be improved by exercise training 3 . Our finding could either indicate reduced levels of fatigue at follow-up or the possibility that some participants learned to overcome the perception of fatigue as a barrier to exercise.…”
Section: Figurementioning
confidence: 99%
“…Cancer treatment is associated with negative physical side effects, including increased fatigue and pain, diminished cardiorespiratory fitness and strength, and negative psychological side effects, including diminished quality of life, anxiety, and depression [1][2][3][4][5] . Many of those side effects can be long-term and can affect health-related quality of life (hrqol) 6 , a concept that encompasses subjective perceptions of both physical and emotional symptoms and side effects of treatment 7 .…”
Section: Introductionmentioning
confidence: 99%